Analisis Bibliometrik Sertifikasi Halal UMKM: Tren, Kontribusi, dan Arah Riset Masa Depan - Hesti Ismawarsih; Luqman Hakim Handoko; Azis Budi Setiawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to map the development of literature related to halal certification in Micro, Small, and Medium Enterprises (MSMEs) through a bibliometric approach based on Google Scholar data. The method used is a combination of quantitative and qualitative approaches (mixed method), with bibliometric techniques for statistical analysis and systematic literature review for thematic interpretation. Secondary data was obtained through the Publish or Perish application, and analyzed using VOSviewer. The results show that from 2017 to November 2024, there were 133 relevant documents. The most productive author is Fajar from Trunojoyo University (4 publications) and the most productive institution is Trunojoyo. The author with the highest citation rate is Alissa Qotrun Nadya (55 citations). Dominant keywords include